PENGEMBANGAN SISTEM KOMUNIKASI DAN RADAR SERTA INSTALASI SENJATA GUNA MENDUKUNG SISTEM PERTAHANAN DAN KEAMANAN RAKYAT SEMESTA (SISHANKAMRATA) - Nunik Nurul Khotimah; Afrizal Hendra; Priyanto (Bajang Institute, 2023)
In this era of globalization, the complexity of technological developments is developing rapidly as well as the fields of communication and radar and weapons installations. Radar is a very useful technology for human life. Radar can be applied to many fields, such as flight systems, weather prediction, navigation of shipping, policing, research, detection of space objects, to the military. The development of the National Radar Industry Center aims to maintain the security of the NKRI region, mastery and independence of technology, meet the needs of domestic and regional markets, to be able to drive the economy in Indonesia. The development of the National Radar Industry can increase GDP (Gross Domestic Product) and economic growth by reducing imports, growing investment and orientation in the future, and creating a workforce. In addition, it can also make foreign exchange savings through contributions to local industries, tax contributions, and become a supply chain on a regional market scale. And of course it will increase the independence of the technology. In accordance with the development of the complexity of Alpahankam. The development is needed in the construction of an equipment integration system known as the integrated concept of C4ISR (Command, Control, Communication, Computer, Intelligence, Surveillance, and Reconnaissance) and implementing Network Centric Warfare (NCW) in accordance with the doctrine and defense needs of the TNI in Indonesia.